Effect of unilateral and simultaneous bilateral cochlear implantation on tinnitus: A Prospective Study. (8th August 2015) - van Zon, Alice; Smulders, Yvette E.; Ramakers, Geerte G. J.; Stegeman, Inge; Smit, Adriana L.; Van Zanten, Gijsbert A.; Stokroos, Robert J.; Hendrice, Nadia; Free, Rolien H.; Maat, Bert; Frijns, Johan H. M.; Mylanus, Emmanuel A. M.; et al.
Abstract : Objectives/Hypothesis: To determine the effect of cochlear implantation on tinnitus perception in patients with severe bilateral postlingual sensorineural hearing loss and to demonstrate possible differences between unilateral and bilateral cochlear implantation. Study Design: Prospective study. Methods: Thirty‐eight adult patients were included in this prospective study, as part of a multicenter randomized controlled trial investigating the benefits of bilateral cochlear implantation versus unilateral cochlear implantation. Pre‐ and postoperative tinnitus perception scores were evaluated, before and 1 year after implantation on three tinnitus questionnaires; the Tinnitus Handicap Inventory (THI), the Tinnitus Questionnaire (TQ), and a visual analogue scale for tinnitus burden. Results: Before implantation, the tinnitus prevalence was 42.1% (16 of 38) in the whole study group. One year after implantation, the tinnitus questionnaire scores had decreased in 71.4% according to the TQ and 80.0% according to the THI. Tinnitus was induced after cochlear implantation in six patients, five in the bilateral and one in the unilateral group. Conclusions: Our study shows that cochlear implantation is effective in the reduction of tinnitus in patients with bilateral sensorineural hearing loss who suffered from preoperative tinnitus. Conversely, tinnitus may also increase or even be induced by the cochlear implantation itself. Cochlear implant candidates should be well informed about these possible consequences before undergoing surgery. Level of Evidence: 2b Laryngoscope, 126:956–961, 2016